Glass sand filter material and preparation method thereof
By performing high-temperature annealing, ultrasonic cleaning and double etching on the glass sand, glass sand filter material with micro-nano binary structure is formed, which solves the problems of antibacterial and short service life of existing quartz sand filter materials in water treatment, and achieves the effect of efficient filtration and long life.
Patent Information
- Application Number
- CN202510043341.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2045-01-10
AI Technical Summary
The existing quartz sand filters are prone to breed bacteria and form mucus during water treatment, which is difficult to backwash and has a large thermal expansion coefficient, which makes them easy to react chemically with iron oxides, resulting in a decrease in filtration effect and a short service life.
Ultrasonic cleaning and vacuum drying of glass sand after high temperature annealing is used. Through dual etching of fluorine-containing salt and activation liquid, a glass sand filter material with a micro-nano binary structure is formed, which increases the specific surface area and surface roughness and controls the surface charge.
It improves filtration accuracy and contamination ability, enhances antibacterial and self-cleaning ability, extends the service life of the filter material, and reduces mucus generation and plate bonding problems.
Smart Images

Figure CN119425228B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of water treatment, and in particular relates to a glass sand filter material and a preparation method thereof. Background Art
[0002] In the process of water treatment, filtration is generally a process of retaining suspended impurities in the water with a granular filter layer such as quartz sand, so as to make the water clear. Quartz sand filter media is easy to breed bacteria and form mucus, and the backwashing operation is difficult. It is often necessary to clean and backwash regularly and replenish the filter media regularly to maintain its continuous filtering effect. At the same time, the thermal expansion coefficient of quartz sand filter media is relatively large, and it is easy to react chemically with iron oxides.
[0003] In view of this, there is an urgent need for a filter material with good filtering effect, antibacterial and long service life. Summary of the invention
[0004] The purpose of the present invention is to provide a glass sand filter material and a preparation method thereof. By preparing a new type of glass sand filter material with a micro-nano binary structure, the filter material has the characteristics of high filtration accuracy, large specific surface area, self-cleaning, strong pollution holding capacity, strong antibacterial ability, etc., which can greatly improve the filtration performance of the filter material and extend the service life of the filter material.
[0005] In order to achieve the above objectives, the present invention particularly adopts the following technical solutions:
[0006] The invention provides a glass sand filter material, wherein the material particles have a rough surface and a micro-nano binary structure; wherein the micron-level structure is a non-uniformly distributed multilayer structure with a pore size of about 2-5 μm; and the nano-level pore size is 5-70 nm.
[0007] Furthermore, the specific surface area of the material is 20-60 m² / g, and the surface of the material particles is negatively charged.
[0008] The present invention also provides a method for preparing the glass sand filter material, comprising the following steps:
[0009] S1: Ultrasonic cleaning of glass sand, after drying, remove impurities and keep the glass surface clean.
[0010] Furthermore, the particle size of the glass sand is 0.5-1 mm.
[0011] Preferably, the ultrasonic cleaning is performed in deionized water.
[0012] S2: subjecting the product obtained in step S1 to high temperature annealing treatment to cause phase separation of the glass, with the sodium-lime phase migrating to the surface for enrichment.
[0013] Furthermore, the temperature of the high temperature annealing treatment is 600° C.-650° C.; the time of the high temperature annealing treatment is 5-7 hours.
[0014] S3: Soak the product obtained in step S2 in a buffer solution to control the reaction rate of the next step.
[0015] Furthermore, the buffer comprises an ethanol solution of one or more of sulfided animal protein, diphosphotoluene thiourea or hexamethylenetetramine.
[0016] Furthermore, the concentration of the buffer solution is 0.05-0.15wt.%.
[0017] Furthermore, the soaking time is 5-10 minutes.
[0018] S4: adding an aqueous solution of a fluoride salt to the buffer solution, continuing to immerse, then taking out, washing, and vacuum drying.
[0019] Aqueous solutions containing fluoride salts can etch micrometer-sized holes, and vacuum drying can avoid the introduction of other impurities.
[0020] Optionally, the fluorine-containing salt includes one or more of Na2SiF6, NH4F, NH4HF2, CaF2 or KF. In particular, by using several fluorine-containing salts at the same time, by adjusting the ratio, the instability of etching efficiency caused by a single component can be avoided, the etching process can be conveniently controlled, and a certain degree of stability can be effectively maintained.
[0021] Furthermore, the soaking time is 10-30 minutes.
[0022] S5: heat-treating the product obtained in step S4.
[0023] Furthermore, the temperature of the heat treatment is 250-350°C; and the time of the heat treatment is 30-60 minutes.
[0024] S6: placing the product obtained in step S5 in an activation solution for reaction.
[0025] During the reaction, the sodium-calcium phase that migrates to the surface of the glass after phase separation reacts with hydrogen ions, changing the ratio of metal ions to silicates and anions, forming a high-silicon layer with a mesoporous structure, and changing the surface charge.
[0026] Optionally, the activation solution includes one or more of nitric acid, sulfuric acid, hydrochloric acid or glacial acetic acid.
[0027] In particular, since the phase separation process of glass is uneven, if you want to react with the precipitated sodium-calcium phase, it is better to use a combination of two acids, such as hydrochloric acid and sulfuric acid. Hydrochloric acid can replace the sodium phase, and sulfuric acid can replace the calcium phase.
[0028] Furthermore, the reaction time is 30-50 min.
[0029] Preferably, the total concentration of the activation solution is 0.02-1 mol / L.
[0030] S7: Soak the product obtained in step S6 in deionized water for multiple times to wash it, and dry it to obtain the product.
[0031] Since the pore size of the glass sand surface is small after the activation liquid reacts, it needs to be soaked to produce the exchange of acid and water and remove the excess acid.
[0032] Compared with the prior art, the present invention performs double etching with fluorine-containing salt and activation solution after high-temperature annealing, and adds a buffer solution to control the rate of the etching reaction, thereby obtaining a filter material with a micro-nano binary structure, thereby increasing the specific surface area of the material and enhancing the dirt holding capacity. The binary structure on the surface of the glass sand filter material increases the surface roughness of the glass sand, and in particular, the presence of the nanopore surface morphology can reduce the surface energy, reduce the contact area between the water droplet and the film, increase the contact angle, and give it hydrophobicity. At the same time, it has self-cleaning and antibacterial capabilities, reduces bacterial attachment, inhibits the formation of biofilms, improves the problem of filter material agglomeration, and extends the service life of the filter material. In addition, its surface carries a negative charge, which improves the filtration accuracy and greatly improves the filtration adsorption effect.
[0033] The raw materials for this application are widely available, and glass sand recycled from waste can be used. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0035] Figure 1 This is an electron microscope photograph of the glass sand filter material of Example 1 of the present invention magnified 302 times;
[0036] Figure 2 This is an electron microscope photograph of the glass sand filter material of Example 1 of the present invention magnified 500 times;
[0037] Figure 3 This is a zeta potential test diagram of Example 1 of the present invention;
[0038] Figure 4 This is a zeta potential test diagram of Example 2 of the present invention;
[0039] Figure 5This is a zeta potential test diagram of Example 3 of the present invention;
[0040] Figure 6 This is a zeta potential test diagram of Comparative Example 1 of the present invention;
[0041] Figure 7 This is a zeta potential test diagram of Comparative Example 2 of the present invention;
[0042] Figure 8 This is a zeta potential test diagram of comparative example 3 of the present invention. DETAILED DESCRIPTION
[0043] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0044] The ratios not given in the examples are all arbitrary ratios, the units of the ratios not given are all mass ratios, and the raw materials are all conventional commercially available products.
[0045] Example 1
[0046] A method for preparing glass sand filter material:
[0047] The 0.5-1 mm glass sand raw material is ultrasonically cleaned with deionized water, dried in an oven at 100°C after cleaning, and then placed in a muffle furnace and heated to 600°C for high-temperature annealing treatment for 5 hours; the annealed glass sand is immersed in the prepared 0.1wt.% sulfided animal protein for 10 minutes; an aqueous solution of 2wt.% Na2SiF6, 2wt.% NH4F, and 2wt.% NH4HF2 is added thereto for 10 minutes, and after the immersion is completed, it is rinsed with deionized water, dried at 100°C in a vacuum drying oven, and then heated to 300°C in a microwave vacuum sintering furnace for heat treatment for 40 minutes; the glass sand is then placed in a mixed solution of sulfuric acid and hydrochloric acid (the ratio of sulfuric acid to hydrochloric acid is 1:1, the concentration of sulfuric acid is 0.05mol / L, and the concentration of hydrochloric acid is 0.2mol / L) and reacted for 30 minutes; finally, it is immersed in deionized water for multiple times, washed, and dried to obtain the glass sand filter material. The electron microscope photo of the glass sand filter material is shown in Figure 1 and Figure 2As shown, the particle surface is rough, with a micro-nano binary structure, a micron-scale pore size of about 2-3μm, a nano-scale pore size of 5-20nm, a specific surface area of 25 m² / g, and a negative charge on the surface, such as Figure 3 As shown, its zeta potential is -48.3 mV.
[0048] Example 2
[0049] A method for preparing glass sand filter material:
[0050] The 0.5-1 mm glass sand raw material is ultrasonically cleaned with deionized water, dried in an oven at 100°C after cleaning, and then placed in a muffle furnace and heated to 630°C for high-temperature annealing treatment for 6 hours; the annealed glass sand is immersed in the prepared 0.05wt.% sulfided animal protein for 8 minutes; an aqueous solution of 2wt.% Na2SiF6, 3wt.% NH4F, and 3wt.% NH4HF2 is added thereto for 20 minutes, and after the immersion is completed, it is rinsed with deionized water and dried in a vacuum drying oven at 100°C, and then the glass sand is heated to 300°C in a microwave vacuum sintering furnace for heat treatment for 60 minutes, and then the glass sand is placed in a mixed solution of sulfuric acid and hydrochloric acid (the ratio of sulfuric acid to hydrochloric acid is 1:3, the concentration of sulfuric acid is 0.02mol / L, and the concentration of hydrochloric acid is 0.5mol / L) and reacted for 40 minutes; finally, it is immersed in deionized water for multiple times, washed, and dried to obtain the glass sand filter material. The glass sand filter material has a micro-nano binary structure, uniform pore size, micron-level pore size of about 2-4μm, nano-level pore size of 20-40nm, specific surface area of 52 m² / g, and negative charge on the surface, such as Figure 4 As shown, its zeta potential is -52.4 mV.
[0051] Example 3
[0052] A method for preparing glass sand filter material:
[0053] The 0.5-1 mm glass sand raw material is ultrasonically cleaned with deionized water, dried in an oven at 100°C after cleaning, and then placed in a muffle furnace and heated to 650°C for high-temperature annealing treatment for 7 hours; the annealed glass sand is immersed in the prepared 0.15wt.% sulfided animal protein for 5 minutes; an aqueous solution of 3wt.% Na2SiF6, 2wt.% NH4F, and 3wt.% NH4HF2 is added thereto for 60 minutes, and after the immersion is completed, it is rinsed with deionized water and dried in a vacuum drying oven at 100°C, and then the glass sand is heated to 300°C in a microwave vacuum sintering furnace for heat treatment for 30 minutes, and then the glass sand is placed in a mixed solution of sulfuric acid and hydrochloric acid (the ratio of sulfuric acid to hydrochloric acid is 1:2, the concentration of sulfuric acid is 0.02mol / L, and the concentration of hydrochloric acid is 1mol / L) for reaction for 40 minutes; finally, it is immersed in deionized water for multiple times, washed, and dried to obtain the glass sand filter material. The glass sand filter material has a micro-nano binary structure, uniform pore size, micron-level pore size of about 4-5μm, nano-level pore size of 20-70nm, specific surface area of 33 m² / g, and negative charge on the surface, such as Figure 5 As shown, the zeta potential is -49 mV.
[0054] Comparative Example 1
[0055] The difference from Example 1 is that the temperature of the high temperature annealing treatment is 550°C. The glass sand filter material has micron-level pores and a very small number of nanopores, the pore size is uneven, the micron-level pore size is about 1-2μm, the nano-level pore size is 2-5nm, the specific surface area is 7 m² / g, and the surface is negatively charged, such as Figure 6 As shown, the zeta potential is -12.3mV, the charge is small, and it is in an extremely unstable state.
[0056] Comparative Example 2
[0057] The difference from Example 1 is that the concentration of the activation solution is different, the ratio of sulfuric acid to hydrochloric acid is 1:3, the concentration of sulfuric acid is 1.5 mol / L, and the concentration of hydrochloric acid is 1.5 mol / L. The glass sand filter material has a micron-level pore size and a small amount of nanopores, the pore size is uneven, and wormholes are formed on the surface. The micron-level pore size is about 5-10 μm, the nano-level pore size is 70-90 nm, the specific surface area is 9 m² / g, and the surface is negatively charged, such as Figure 7 As shown, the zeta potential is -22.8mV, the charge is small, and it is in an unstable state.
[0058] Comparative Example 3
[0059] Using the glass sand raw material, the zeta potential test is as follows Figure 8As shown, the zeta potential is -0.8 mV, the charge is extremely low, and the fluctuation of the potential curve indicates that the potential difference between the continuous phase and the fluid stable layer attached to the dispersed particles is in an unstable state, which also reflects that the surface of the glass sand raw material does not have a nanostructure.
[0060] Table 1 Performance of Examples and Comparative Examples
[0061]
[0062] Combined with Table 1, since the annealing process affects the phase separation process, the high temperature annealing treatment temperature of Comparative Example 1 is low, and no segregation phenomenon occurs. After the micron pores are formed, no chemical reaction occurs in the second step, and corrosion still occurs. Only a small amount of nanopores are formed, the charge is small, and the specific surface area is low. Due to the excessively high acid concentration in Comparative Example 2, the reaction is uneven, the pore size of the nanopores is greatly enlarged, and the specific surface area is larger than that of Comparative Example 1, but the charge is still in an unstable state.
[0063] Please note that the technical features of the above embodiments can be combined arbitrarily. In order to make the description concise, all possible combinations of the technical features in the above embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. The above embodiments only express several implementation methods of the present application, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several variations and improvements can be made, which all belong to the scope of protection of the present application. Therefore, the scope of protection of the patent in this application shall be based on the attached claims.
Claims
1. A method for preparing a glass sand filter material, characterized in that: The steps include: S1: Ultrasonic cleaning of glass sand, and keeping the glass surface clean after drying; S2: subjecting the product obtained in step S1 to high temperature annealing treatment to cause phase separation of the glass; the temperature of the high temperature annealing treatment is 600° C.-650° C.; S3: soaking the product obtained in step S2 in a buffer solution; S4: adding an aqueous solution of a fluoride salt to the buffer solution, continuing to immerse, then taking out, washing, and vacuum drying; S5: heat treating the product obtained in step S4; S6: placing the product obtained in step S5 in an activation solution for reaction; the activation solution comprises one or more of nitric acid, sulfuric acid, hydrochloric acid or glacial acetic acid; the total concentration of the activation solution is 0.02-1 mol / L; S7: Soak the product obtained in step S6 in deionized water for cleaning and drying.
2. The preparation method according to claim 1, characterized in that: In step S1, the particle size of the glass sand is 0.5-1 mm; And / or, the ultrasonic cleaning is performed in deionized water.
3. The preparation method according to claim 1, characterized in that: In step S2, the high temperature annealing treatment is performed for 5-7 hours.
4. The preparation method according to claim 1, characterized in that: In step S3, the buffer comprises an ethanol solution of one or more of sulfided animal protein, diphosphotoluene thiourea or hexamethylenetetramine; and / or, the concentration of the buffer is 0.05-0.15wt.%; And / or, the soaking time is 5-10 minutes.
5. The preparation method according to claim 1, characterized in that: In step S4, the fluorine-containing salt includes one or more of Na2SiF6, NH4F, NH4HF2, CaF2 or KF; And / or, the continued soaking time is 10-30 minutes.
6. The preparation method according to claim 1, characterized in that: In step S5, the temperature of the heat treatment is 250-350° C.; the time of the heat treatment is 30-60 min.
7. The preparation method according to claim 1, characterized in that In step S6, the reaction time is 30-50 min.
8. A glass sand filter material, characterized in that: The glass sand filter material is prepared by the preparation method according to any one of claims 1 to 7, wherein the surface of the glass sand filter material particles is rough and has a micro-nano binary structure; wherein the micron-level structure is a non-uniformly distributed multilayer structure with a pore size of 2-5 μm; and the nano-level pore size is 5-70 nm.
9. The glass sand filter material according to claim 8, characterized in that: The specific surface area of the material is 20-60 m² / g, and the surface of the material particles is negatively charged.
Citation Information
Patent Citations
Modified glass filter material for oilfield sewage treatment and preparation method thereof
CN111097230A
Processing method for prolonging service life of quartz product for LPCVD (Low Pressure Chemical Vapor Deposition) process
CN113213736A